INTEGRITY (DOBROCHESNIST) OF A PUBLIC SERVANT: ETHICAL AND LEGAL DIMENSIONS - Korchak, Natalia; Parkhomenko-Kutsevil, Oksana (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: analysis of integrity (dobrochesnist – in Ukrainian) as a moral and ethical component of the public servant, which defines the limit and forms a legitimate model of his behavior. Methods: analysis, synthesis, induction, deduction, abstraction, concretization, generalization. Results: author’s conclusions about the peculiarities of the interaction of morality and law as regulators of the behavior of public servants and the need to take into account integrity and ethics in the implementation of qualitative characteristics of their behavior. Discussion: the issue of ethical and legal dimensions of civil servant integrity is closely related to the relationship and interaction of morality and law in the system of socio-normative regulation. The rules of professional ethics should be considered as a legalization of moral qualities, values and obligations of a public servant. Through the introduction of rules of ethical behavior, the state tries to stimulate motivation for lawful (virtuous) behavior. A public servant must be aware of the need to be guided in his / her activity by the system of values, principles, norms and attitudes, defined in the relevant normative legal acts and fixed in the codes or standards of professional ethics. Integrity is a moral and ethical component of a public servant’s activity, which determines the limit and manner of his behavior. Solving the problem of the integrity of government through the improvement of public service institutions, statutory ethical regulators of public servants and standards of their integrity. Preventing corruption is primarily about boosting integrity.The role of the National Agency for the Prevention of Corruption in the institutionalization of integrity standards is growing. The Agency is working to raise these standards and constantly reminds them of the need to comply with them.